Efficacy of flaxseed supplement on the lipid profile of hyperlipidemic subjects - Lakshmi V (Department of Home Science, College of Agriculture, 2007)
The present study entitled “Efficacy of flaxseed supplement on the lipid profile of hyperlipidemic subjects” was undertaken with an objective to assess the impact of flaxseed supplement on the blood lipid profile of hyperlipidemic subjects.